Conscientious Refusals and Reason-Giving - Marsh, Jason (Bioethics, 2014)
Some philosophers have argued for what I call the reason-giving requirement for conscientious refusal in reproductive healthcare. According to this requirement, healthcare practitioners who conscientiously object to administering standard forms of treatment must have arguments to back up their conscience, arguments that are purely public in character. I argue that such a requirement, though attractive in some ways, faces an overlooked epistemic problem: it is either too easy or too difficult to satisfy in standard cases. I close by briefly considering whether a version of the reason-giving requirement can be salvaged despite this important difficulty.